RITUXIMAB: NEW RESOURCES OF MANAGEMENT OF SEVERE REFRACTORY JUVENILE RHEUMATOID ARTHRITIS - E.I. Alexeeva; T.М. Bzarova; S.I. Valieva; K.B. Isaeva; A.M. Chomakhidze; E.L. Semikina ("Paediatrician" Publishers LLC, 2008)
The management of severe juvenile rheumatoid arthritis (JRA) is a complicated problem. The efficacy and safety of Rituximab was investigated in 32 infliximabrefractory patients with different types of JRA, who had failed standard immunosuppressive therapy. Rituximab induced remission in 52% of patients. Rituximab was well tolerated, some patients experienced infusionbrelated adverse events, infections of upper airways and neutropenias. It's recommended to carry out a management of patients with JRA in specialized rheumatological centers with modern diagnostic and medicamental technologies because of subsequent adverse events.Key words: children, management, rituximab, B cells, juvenile rheumatoid arthritis.